Prediabetes: Challenges, Novel Solutions, and Future Directions - Monique E Francois; Katie M Oetsch (European Medical Journal)
Prediabetes: Prediabetes is a salient state of hyperglycaemia and/or hyperinsulinaemia that often precedes a diagnosis of Type 2 diabetes (T2D). It is projected that by 2040, almost 8% of the global population will have prediabetes, with approximately 70% progressing to T2D within their lifetime. Abnormal glucose tolerance increases the risk of associated complications, including cardiovascular disease, stroke, and microvascular diseases, all of which are major contributors to the global healthcare burden. T2D alone is predicted to cost the healthcare system upwards of 490 billion USD by 2030, thus addressing this growing burden is vital. Challenge One. Diagnosis and classification: Diagnosis poses a challenge and there is debate between leading world expert panels regarding thresholds, notably between the World Health Organization (WHO) and American Diabetes Association (ADA) for impaired fasting glucose. Hyperinsulinaemia may also go undetected as this is not currently routinely tested or used as diagnostic criteria. This has been largely due to cost and lack of consensus data for appropriate diagnostic threshold; however, with disease burden costs estimated to be close to half a billion USD by the end of the decade, an in-depth cost analysis for benefits-costs of early detection and treatment or prevention is warranted. Challenge Two. Health messaging and public perception: Prediabetes can revert to normoglycaemia with diet and lifestyle interventions. This, however, is not conveyed well in public health messaging. In addition to public perception about the likelihood of disease progression to T2D, prediabetes is not considered a disease state, which may also influence public perception regarding perceived urgency of treatment and necessity for intervention. Challenge Three. Intervention and treatment: Diet and lifestyle interventions are heralded as best practice when it comes to prediabetes management, and metformin for those at greatest risk of future T2D. Synergistic use of the available novel and promising interventions including low carbohydrate diets, higher protein diets, time restricted feeding, and high intensity interval training may help time-poor individuals achieve improvements in risk-factors including weight loss and glycaemic control (HbA1c and fasting plasma glucose). As large-scale feasibility and adherence are major obstacles to contend with in the rollout of diet and lifestyle interventions, personalised approaches, coupled with counselling based on social cognitive theory, may be increasingly utilised to target specific groups and individuals as programmes can be tailored to meet specific needs and preferences.